Antagonising Yin Yang 1 ameliorates the symptoms of lupus nephritis via modulating T lymphocyte signaling - Haoxing Yuan; Zheng Peng; Meilian Zhang; Honglian Li; Kunyu Lu; Chan Yang; Minmin Li; Shuwen Liu (Elsevier, 2024)
Lupus nephritis (LN) is a chronic complication of systemic lupus erythematosus (SLE). At present, no drugs are capable of delaying the progression of LN without a risk of serious side effects. There is thus a pressing need for further studies of LN pathogenesis to identify novel therapeutic targets and aid in the development of new approaches to treating this debilitating disease. In this study, a multi-omics approach was used to characterize the pathogenesis of LN and to identify disease-related targets, ultimately leading to the identification and validation of Yin Yang 1 (YY1) as a promising therapeutic target in LN. A rapid approach to efficiently screening for candidate YY1 ligands was implemented using drug databases that established rebamipide as a YY1 antagonist suitable for use in the management of LN. Specifically, the YY1 antagonist activity of rebamipide was found to regulate lymphocyte activity, reduce autoantibody production, limit immune complex deposition, and suppress macrophage activation while improving symptoms in a murine model of LN. Results supportive of a similar pathologic mechanism of action were also obtained when analyzing renal tissue sections from LN patients, underscoring the potential clinical significance of YY1 and its antagonist rebamipide, suggesting that rebamipide may have positive effects on lymphocytes and may improve symptoms in treated patients. This study provides a robust foundation for further research focused on the pathogenesis and treatment of LN.